Cellular Transcription Factor YY1 Mediates the Varicella-Zoster Virus (VZV) IE62 Transcriptional Activation - Khalil, Mohamed I. (2013)
Several cellular transcription factors have been shown to be involved in IE62-mediated activation. The YY1 cellular transcription factor has activating and repressive effects on gene transcription. Analysis of the VZV genome revealed 19 postulated YY1 binding sites located within putative promoters of 16 VZV genes. Electrophoretic mobility shift assays (EMSA) confirmed the binding of YY1 to ORF10, ORF28/29 and gI promoters and the mutation of these binding sites inhibited YY1 binding and the promoter activation by IE62 alone or following VZV infection. Mutation of the ORF28/29 YY1 site in the VZV genome displayed insignificant influence on virus growth in melanoma cells; but it inhibited the virus replication significantly at day 5 and 6 post infection in HELF cells. This work suggests a novel role for the cellular factor YY1 in VZV replication through the mediation of IE62 activation of viral gene expression.